Priority Directions for Life Insurance Development in Uzbekistan - Mirzaeva Azizakhon; Mirzamakhmudova Madina (Proceedings of the International Conference on Applied Innovations in IT, 2025)
The article was prepared within the framework of the practical project of AL-7823051642 “econometric modeling and forecasting of demand for insurance services in Uzbekistan on the basis of socio-economic and demographic factors” performed at the National University of Uzbekistan named after Mirzo Ulugbek.In this paper, the authors analyze the formation of life insurance in Uzbekistan, the ongoing reform of the insurance market of the republic, and ways of accelerating its development. It also looks at the development of higher-demand life insurance services. The paper examines the main drivers of insurance industry modernization, innovative product lines, regulatory modernization, and the importance of new digital technologies for increasing availability and quality of insurance services. The main risks in the activities of life insurance companies in Uzbekistan are insufficient literacy rate of society, frequent changes in laws and regulatory documents regulating the insurance industry in Uzbekistan, increased prices for raw materials and services of insurance companies, the presence of high financial, natural disasters and environmental risks in Uzbekistan,. it was found to be technology-related risks. In order to study the development of the insurance market in Uzbekistan, the relationship between GDP, inflation and demand for insurance services in the country was analyzed. According to him, an increase in GDP develops the insurance market, increases demand and volume. Inflation, on the other hand, increases risks in the insurance market, assuming a balance between premiums and payments. The results intended for calling attention to strategic ways how to increase the strength of the insurance sector, to support the economic stability and to increase insurance awareness of life insurance in Uzbekistan.